Characterization of changes in metabolic pathways during dengue virus serotype 2 infection of the Aedes aegypti mosquito vector to identify control points for interrupting virus transmission - Chotiwan, Nunya, author; Perera, Rushika, advisor; Blair, Carol, committee member; Foy, Brian, committee member; Huang, Claire, committee member; Di Pietro, Santiago, committee member (Colorado State University. Libraries, 2018)
Dengue viruses (DENV) are mosquito-borne viruses that cause a wide range of acute symptoms from mild fever to lethal dengue shock syndrome in humans. DENV are transmitted primarily by Aedes aegypti (Ae. aegypti). These mosquitoes are widely distributed throughout tropical and subtropical areas around the world. Increasing globalization, urbanization and global warming are factors that enhance the spread of these vectors placing over 2.5 billion people at risk of contracting these viruses. Transmission of these viruses depends on their ability to infect, replicate and disseminate into several tissues in the mosquito vector. During DENV infection of its human and mosquito hosts, a visible rearrangement of lipid membrane architecture and alterations of the metabolic repertoire is induced. These events occur to facilitate efficient viral replication and virus assembly within the cell and to circumvent antiviral responses from the host. Interference with these virus-induced processes can be detrimental to virus replication and can prevent viral transmission. In this dissertation, we present the first insight into the metabolic environment induced during DENV serotype 2 (DENV2) replication in Ae. aegypti. Using untargeted high-resolution liquid chromatography-mass spectrometry, we explored the temporal metabolic perturbations that occur following dengue virus infection of the midgut, the primary site of the virus infection in the mosquito vector. Temporal changes of metabolites across early-, mid- and late-infection time points were identified. A marked increase in the /content of glycerophospholipids, sphingolipids and fatty acyls was coincident with the kinetics of viral replication. Elevation of glycerolipid levels and the accumulation of medium-chain acyl-carnitines suggested a diversion of resources during infection from energy storage to synthetic pathways and energy production. From the observations above, two active pathways, sphingolipid and de novo fatty acid synthesis pathways, were further validated to identify metabolic control hubs. Using inhibitor screening of the sphingolipid pathway, we determined that sphingolipid Δ-4 desaturase (DEGS), the enzyme that converts dihydroceramide to ceramide was important for DENV2 infection in cultured Ae. aegypti cells (Aag2). Long, double-stranded RNA-mediated knockdown of DEGS expression led to the imbalance of ceramide to dihydroceramide ratios and affected DENV2 infection in cell culture. However, the inhibitory effect to DENV2 replication was not observed during DEGS-knockdown in mosquito vectors. De novo fatty acid biosynthesis is the pathway that synthesizes the first lipid molecules, fatty acids, required in synthesizing complex lipid molecules, such as glycerophospholipids, glycerolipids and sphingolipids. As a result, this pathway serves as a bottle neck for the control of lipid metabolism. In this study, we annotated and characterized the expression of seven Ae. aegypti fatty acid synthase (AaFAS) genes in the different stages of mosquito development and upon exposure to different diets. We found that AaFAS1 shares the highest amino acid similarity to human fatty acid synthase (FAS) and is the dominant AaFAS that expressed in female mosquitoes. Knockdown expression of AaFAS1 expression showed a reduction in DENV2 replication in the Aag2 cells and in the midgut of Ae. aegypti mosquitoes during early infection. However, the correlation between viral infection and levels of AaFAS1 expression was difficult to elucidate. The work in this dissertation has highlighted metabolic pathways that are induced by DENV2 infection and the metabolic control points within these pathways that are critical for DENV2 infection in Ae. aegypti. Successful perturbation of metabolic homeostasis can potentially limit virus replication in the vector, presenting a novel avenue to block the transmission of DENV2 from the mosquitoes to humans.
Keywords: lipid metabolism; mosquito; flavivirus; Dengue; Aedes aegypti